2003
DOI: 10.1095/biolreprod.102.005934
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Regulation of Milk Composition, Milk Production, and Pouch Young Development During Lactation in the Tammar Wallaby (Macropus eugenii )1

Abstract: Specific changes in milk composition during lactation in the tammar wallaby (Macropus eugenii) were correlated with the ages of the developing pouch young (PY). The present experiment was designed to test the hypothesis that the sucking pattern of the PY determines the course of mammary development in the tammar wallaby. To test this hypothesis, groups of 60-day-old PY were fostered repeatedly onto one group of host mothers so that a constant sucking stimulus on the mammary gland was maintained for 56 days to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 24 publications
4
77
0
2
Order By: Relevance
“…We know that the lactating tammar regulates these changes in milk composition, which in turn determines the rate of pouch young growth and development. If a pouch young at an early stage of lactation is transferred to the mammary gland of a tammar at a later stage of lactation, the fostered young will grow and develop at an accelerated rate (3). Much of the equivalent development in eutherians occurs in utero.…”
Section: The Tammar As a Model System To Study Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that the lactating tammar regulates these changes in milk composition, which in turn determines the rate of pouch young growth and development. If a pouch young at an early stage of lactation is transferred to the mammary gland of a tammar at a later stage of lactation, the fostered young will grow and develop at an accelerated rate (3). Much of the equivalent development in eutherians occurs in utero.…”
Section: The Tammar As a Model System To Study Lactationmentioning
confidence: 99%
“…Phase 3 of lactation (200 -330 days) is characterized by dramatic changes in milk production and composition with an elevated level of protein and lipid and low levels of carbohydrate (3,4). Broadly there are two groups of milk protein genes expressed during the lactation cycle; one group of genes is induced to high levels around parturition and expressed throughout lactation, and a second group of genes are expressed only during specific phases of lactation (Fig.…”
Section: Milk Protein Gene Expression: Naturally Occurring Gene Knockmentioning
confidence: 99%
“…Teniendo como referencia el trabajo de Trott et al (2003), el período de lactancia de estos organismos se puede dividir en cuatro fases. La fase 1 corresponde a la gestación cuyo proceso es de cerca de 26 días tiempo en el que las cuatro glándulas mamarías de la hembra preñada se preparan para la lactancia y producen calostro.…”
Section: Glándulas Mamariasunclassified
“…There is concomitant growth and development of the mammary gland in the quokka as in other macropods over this period. This could simplistically be attributed to a 'demand and supply' response of the mammary gland to the increasing appetite of the young joey; however, it has been demonstrated in the tammar wallaby that the mother exercises considerable control of the development of the young through inherent sequential changes in milk composition (31) . In contrast, wild rabbits (Oryctolagus cuniculus (L.)) usually suckle about six young in a litter.…”
Section: Duration Of Lactation and Neonatal Growthmentioning
confidence: 99%
“…It has been found that when younger animals are fostered onto lactating females (that were at a more advanced stage of lactation) gross milk composition and secretion of specific milk proteins remained unchanged and the developmental rate of the fostered young dramatically increased (31) . Therefore, the female tammar regulates the functional development of the mammary gland during lactation and the synthesis and secretion of milk in turn regulates the development of the young regardless of its age.…”
Section: 'Altricial' Neonatal Metabolismmentioning
confidence: 99%